Prognostic value of worsening renal function in outpatients with chronic heart failure - Pimentel, R (2014)
Introduction and objectives: Renal function impairment predicts poor survival in heart failure. Attention has recently shifted to worsening renal function, based mostly on serum creatinine and estimated glomerular filtration rate. We assessed the prognostic effect of worsening renal function in ambulatory heart failure patients. Methods: Data from 306 ambulatory patients were abstracted from medical files. Worsening renal function was based on the change in estimated glomerular filtration rate, serum creatinine and urea within 6 months of referral. Prognosis was assessed by the composite endpoint all-cause death or heart failure hospitalization, censored at 2 years. Hazard ratios were estimated for worsening renal function, adjusted for sex, age, diabetes, New York Heart Association class, left ventricular systolic dysfunction, medications and baseline renal function. Results: The agreement among definitions was fair, with kappa coefficients generally not surpassing 0.5. Worsening renal function was associated with poor outcome with adjusted hazard ratios (95% confidence interval) of 3.2 (1.8–5.9) for an increase of serum creatinine > 0.3 mg/dl; 2.2 (1.3–3.7) for an increase in serum urea > 20 mg/dl and 1.9 (1.1–3.3) for a decrease in estimated glomerular filtration rate > 20%, independent of baseline renal function. The 2-year risk of death/heart failure hospitalization was approximately 50% in patients with an increase in serum creatinine or in serum urea; this positive predictive value was higher than for decreasing estimated glomerular filtration rate. Conclusions: In conclusion, worsening renal function was significantly associated with a worse outcome. Different definitions identified different patients at risk and increasing creatinine/urea performed better than decreasing estimated glomerular filtration rate.